Perancangan Sistem Informasi Keuangan Dan Kas Sekolah (SIKAS) Berbasis Desktop - Rahmat Ferdiyansyah; Ahmad Alwi Tio Wicaksono; Muhammad Hestiavin Daffa; Rizky Basatha; Nisa Dwi Septiyanti (Journal Of Informatics And Busisnes, 2025)
Financial and cash management in schools, such as recording student fees, BOS funds, and operational expenses, is often still done manually. This manual process is prone to recording errors (human error), takes a long time to recapitulate, and makes it difficult to prepare financial reports quickly and accurately. This study aims to design and implement a desktop-based information system called SIKAS (School Financial and Cash Management System) to address these issues. This application was built using the Visual Basic (VB.NET) programming language with a MySQL database management system. The result of this research is a functional SIKAS desktop application capable of managing master data, recording income and expenditure transactions, and automatically generating monthly financial reports. With the SIKAS system, it is hoped that the financial administration process in schools can run more efficiently, effectively, and accurately.